Studies on bus services and passenger demand sustainability - Muhammad Adib, Mahmud (2010)
People along Kuantan - Gambang road always have a problem to get bus transportation. They need to wait for a long time to get a bus service. Sometimes, the bas that pass by the Kuantan - Gambang road is always late to arrive at a certain destination. This will make many of people would use personal transport rather than using the bus transportation. Extension from this, the rate of congestion along Kuantan - Gambang road will keep increasing causing by the personal transport such as car, motorcycle, van and Lorries. Beside, the facilities for the bus such as bus stop, is not enough. Certain place did not have a bus stop although the passenger always waits for bus at that place. The comfortable of bus passenger must be maintained so that the quality of bus service could be enhanced and this will attract more passengers to use the bus. This study is to identify the time for bus journey for bus that pass by the Kuantan - Gambang road in certain time, the total passenger use the bus, and identify a suitable location to place a bus stop and the frequency of bus stop use by the passenger. A special table has been made to collect the data such as time, total passenger, type of bus, list of bus stop along Kuantan - Gambang road and bus schedule for arrive and depart to Kuantan town. Passenger calculation for on or off from the bus is already use in developed countries to measure the rate of bus usage as well as enchance the management of bus staff from time to time. This calculation is use in building such as library, the supermarket, commuter station, and airport. The result of studies show that the rate of bus usage in Gambang area is not encouraging because of lack in bus facilities and the time for bus Journey is not suitable. From this studies, the bus schedule could be identify, total passenger use the bus and bus stop can be provide in a strategic location can be identify. Thus, i would like to proposed so that this studies is applies for each transport services such as train, airport, and bus especially to increase the rate of bus usage in Malaysia.